Pengaruh Perceived Deception Dan Kredibilitas Perusahaan Terhadap Sikap Dan Niat Seseorang Mengikuti Undian Berhadiah - Dany Mochamad Darda; Gancar Candra Premananto (Universitas Airlangga, 2015)
Marketing activity is an element that attributed in a business. So it can be said that the success of a company can not be separated from marketing strategies applied. But in it’s development, marketing activities not only regarded as a creative process, but also has a negative side. Or that are specifically concerned about sales promotion that is sweepstakes. That the sweepstakes activities are currently considered can be manipulated or tends to deceive. So this raises the perceived deception for consumers. This means that can lead a person does not believe in the sweepstakes which in turn can affect the person's attitude and intentions in a sweepstakes organized by the company.This study aims to investigate the effect of perceived deception of sweepstakes and corporate credibility on attitude and intention consumer’s to participate sweepstakes. This research was conducted with the experimental design. The study also involved 183 adolescents who liked the snack as a participants, particular teenagers who come from students of s1 in Faculty of Economics and Business, University of Airlangga. Which further data in this study were tested using the Partial Least Square (PLS).The analysis showed that the perceived deception doesn’t have effect on corporate credibility as the organizer of sweepstakes activity. But perceived deception have negative effect on person’s attitude towards sweepstakes. Furthermore corporate credibility have positive effect on attitude towards sweepstakes. Then the attitude also effective in influencing person’s intention in participating in a sweepstakes held.